THE HARMONIZATION OF COOPERATIVE LAW IN THE MERCOSUR AND THE PRINCIPLE OF COOPERATION AMONG COOPERATIVES - Teixeira, Marianna Ferraz; Teixeira , Marília Ferraz; Jaloretto, Mariana Avelar (International Journal of Cooperative Law, 2023)
The present work aims to analyze how the effective harmonization of laws within the scope of Mercosur can favor cooperation among cooperatives inserted in such economic bloc, promoting, in the first instance, the development of cooperativism, so that it becomes possible to face the challenges to come and, as a consequence, enabling regional growth. To this end, the Mercosur recommendations on this matter and its correlation with the Cooperative Laws, among its member countries, will be analyzed. Furthermore, it is also intended to address the extent to which the insertion of rules of Community Law in local lawsand regulations can create a friendly environment in favor of intercooperation, especially due to new technological advances. On the other hand, the possible obstacles to the harmonization of laws to take placewill be also analyzed, having in mind that Mercosur was established in 1991, the Statute of MERCOSUR Cooperativeshas existed for 13years and, yet, none of those main principles set forth in the Statute were effectively fulfilled.